Developing reading comprehension in English with Focus on Pupils with Dyslexia - Eisová, Nikol (Univerzita Pardubice, 2022)
This bachelor thesis focuses on the problematics of the development of reading comprehension and how pupils with dyslexia are being addressed during the process in the classroom. The theoretical part elaborates on dyslexia, its features, and dyslexic learners. It also introduces reading comprehension as a skill, its context in the English language, and approaches of how it should be taught. The final part of the theoretical part discusses the problematic of textbook and its evaluation. The objective of the practical part is to create a checklist of criteria, based on the theoretical part, and evaluate the reading comprehension exercises in the textbook More 2, second edition. Based on the criteria, its suitability for teaching reading comprehension to pupils with dyslexia will be judged. In the final part of the practical section of the thesis, there are proposed possible modifications of three of the evaluated exercises.
Rozvoj řečové dovednosti čtení s porozuměním v anglickém jazyce u žáků s dyslexií
Keywords: dyslexie; cteni s porozumenim; ucebnice; hodnoceni; cviceni pro cteni s porozumenim; seznam kriterii; dyslexia; reading comprehension; textbook; evaluation; reading comprehension exercises; criteria checklist